MEREKONTRUKSI PENGETAHUAN SAINS ILMIAH BERBASIS BUDAYA DAN KEARIFAN LOKAL DI KEPULAUAN KARIMUNJAWA SEBAGAI WAHANA MENUMBUHKAN SOFT SKILL KONSERVASI - Sudarmin, Sudarmin; Mastur, Zaenuri; Parmin, Parmin (Universitas Negeri Semarang, 2014)
This study aims to reconstruct a new theory concerning the basic science of science based on local wisdom in Karimunjawa as a vehicle to grow Soft skills conservation. This study is a qualitative research etnosains with community and environmental settings in Karimun Islands. The study subjects consisted of fishermen, tour guides, as well as the homestay owners. Retrieval of data through interviews, direct observation, and questionnaires. The data obtained and verified, is reduced, and conceptualization. The focus of research is the moral message of conservation that is placed on the bulletin board in the Karimunjawa National Park; Manggrove forest, beach Karimunjawa. In this study also revealed the types of indigenous flora and fauna, as well as soft skills and habits of society Publications. The results of the study found that the value of soft skills such karimunjawa community is working hard, persevering, mutual cooperation. religious, friendly, caring and nurturing environment. The results showed that the conservation of moral message posted on the bulletin board in the Karimunjawa National Park is the conservation of sea turtles, marine fish, marine life, and a variety of coral reef Karimunjawa results also found that local knowledge is still maintained in the plant community dewandaru, Setigi, kalimosodho, soft skills and love of the nation, caring environment, religius, friendly, work hard , and democratic.